2011
DOI: 10.3892/ol.2011.361
|View full text |Cite
|
Sign up to set email alerts
|

Definitive chemoradiotherapy of limited-disease small cell lung cancer: Retrospective analysis of new predictive factors affecting treatment results

Abstract: Abstract. The aim of this study was to evaluate potential predictive factors in the treatment of limited-disease small cell lung cancer (LD-SCLC). A total of 33 patients with LD-SCLC who underwent definitive chemoradiotherapy at our institute between April 1996 and May 2007 were enrolled in our retrospective study. The relationship between a range of potential predictive factors and the initial response, time to progression and pattern of failure was analyzed. The factors evaluated included the tumor markers P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Murray et al . reported that the prolongation of SER (time between the start of any treatment and the end of radiation therapy) resulted in more frequent brain metastasis, and a study from Japan yielded similar results, causing the author to speculate that SER affects survival because of the probability of distant metastasis, but not local control . This tendency was also demonstrated in our study; specifically, the DM rates in the late TRT group were significantly higher than those in the early TRT group, and the LRR rates were not significantly different between the two groups.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Murray et al . reported that the prolongation of SER (time between the start of any treatment and the end of radiation therapy) resulted in more frequent brain metastasis, and a study from Japan yielded similar results, causing the author to speculate that SER affects survival because of the probability of distant metastasis, but not local control . This tendency was also demonstrated in our study; specifically, the DM rates in the late TRT group were significantly higher than those in the early TRT group, and the LRR rates were not significantly different between the two groups.…”
Section: Discussionsupporting
confidence: 84%
“…Patients who received early TRT typically presented with good hematopoietic function and could tolerate concurrent chemoradiotherapy, and it is widely known that concurrent chemoradiotherapy is superior to a sequential regimen in the treatment of SCLC . More importantly, patients in the early TRT group had short durations between the start of chemotherapy and radiotherapy administration, which has been demonstrated to affect survival in several previous studies . Murray et al .…”
Section: Discussionmentioning
confidence: 99%
“…Among the clinical factors that may affect limitedstage SCLC, the size of the tumor and local lymph node metastasis may be the most important prognostic factors. In 2007, the IASLC used the seventh edition of Lung Cancer TNM staging to evaluate SCLC's prognosis (7,8) retrospectively. A total of 12,620 cases were included, of which 8,088 were suitable for TNM staging.…”
Section: Discussionmentioning
confidence: 99%
“…And they were further divided into early RT or late RT groups based on the time thoracic RT was initiated. Early RT included patients who received RT before the beginning of the 4 th cycle of chemotherapy and late RT included patients who received RT after the beginning of the 4 th cycle of chemotherapy ( 6 , 7 ).…”
Section: Methodsmentioning
confidence: 99%